Temporal Regulation of Natural Killer T Cell Interferon Gamma Responses by β-Catenin-Dependent and -Independent Wnt Signaling - Kling, Jessica C.; Jordan, Margaret A.; Pitt, Lauren A.; Meiners, Jana; Thanh-Tran, Thao; Tran, Le Son; Nguyen, Tam T. K.; Mittal, Deepak; Villani, Rehan; Steptoe, Raymond J.; Khosrotehrani, Kiarash; Berzins, Stuart P.; et al. (Frontiers in Immunology, 2018)
Natural Killer T (NKT) cells are prominent innate-like lymphocytes in the liver with critical roles in immune responses during infection, cancer and autoimmunity. IFN-g and IL-4 are key cytokines rapidly produced by NKT cells upon recognition of glycolipid antigens presented by antigen presenting cells (APCs). It has previously been reported that the transcriptional co-activator b-catenin regulates NKT cell differentiation and functionally biases NKT cell responses towards IL-4, at the expense of IFN-g production. b-catenin is a central effector of Wnt signaling but also contributes to other signaling networks. It is currently unknown whether Wnt ligands regulate NKT cell functions. We thus investigated how Wnt ligands and b-catenin activity shape liver NKT cell functions in vivo in response to the glycolipid antigen, a-galactosylceramide (a-GalCer) using a mouse model. Pharmacologic targeting of b-catenin activity with ICG001, as well as myeloid-specific genetic ablation of Wntless (Wls), to specifically target Wnt protein release by APCs, enhanced early IFN-g responses. In contrast, within several hours of a-GalCer challenge, myeloid-specific Wls deficiency, as well as pharmacologic targeting of Wnt release using the small molecule inhibitor IWP-2 impaired a-GalCer-induced IFN-g responses, independent of b-catenin activity. These data suggest that myeloid cell-derived Wnt ligands drive early Wnt/b-catenin signaling that curbs IFN-g responses, but that, subsequently, Wnt ligands sustain IFN-g expression independent of b-catenin activity. Our analyses in ICG001-treated mice confirmed a role for b-catenin activity in driving early IL-4 responses by liver NKT cells. However, neither pharmacologic or genetic perturbation of Wnt production affected the IL-4 response, suggesting that IL-4 production by NKT cells in response to a-GalCer is not driven by released Wnt ligands. Collectively, these data reveal complex temporal roles of Wnt ligands and b-catenin signaling in the regulation of liver NKT cell activation, and highlight Wnt-dependent and –independent contributions of b-catenin to NKT cell functions.